Historia y Antropología : las fronteras de América del Norte. - Jiménez Núñez, Alfredo (Revista Española de Antropología Americana, 2003)
Frontier phenomena are a good touchstone to test the possibility and convenience of interdisciplinary approaches and of processual studies. The frontiers of North America, understood as a hemisphere, offer a field which lends itself especially to research by history and anthropology, the latter through all its branches: archaeology, ethnohistory, ethnology, and linguistics. Americanist historians and anthropologists share a historical continuum, a distinct thematic arena, and rich documentary resources. Two frontiers stand out among the many frontiers of North America: The North of New Spain and the Anglo-American Frontier. Their comparative analysis can draw attention to significant historiographical issues, encourage interdisciplinary research, and help developing frontier theory.